2005
DOI: 10.1007/s00192-005-0046-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term anatomical and functional assessment of trans-vaginal cystocele repair using a tension-free polypropylene mesh

Abstract: We report a case series of 63 women with cystocele who underwent the same trans-vaginal procedure between October 1999 and October 2002. The polypropylene mesh (GyneMesh, Gynecare, Ethicon, France) was placed from the retropubic space to the inferior part of the bladder in a tension-free fashion. Patients were followed up for 24 to 60 months, with a mean follow-up of 37 months. Fifty-five patients returned for follow-up (87.3%). At follow-up, 49 women were anatomically cured (89.1%), five women had stage 2 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
63
0
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 14 publications
8
63
0
11
Order By: Relevance
“…The procedure was found to improve the associated urinary and pelvic floor symptoms. The excellent anatomical results of our study correspond with the 89% objective cure rate reported by de Tayrac et al [10], whose study had a mean follow-up period of 37 months. Short-term and medium-term cure rates for anterior vaginal wall repair with a Gynemesh TM PS range from 90% to 100% [10][11][12][13].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The procedure was found to improve the associated urinary and pelvic floor symptoms. The excellent anatomical results of our study correspond with the 89% objective cure rate reported by de Tayrac et al [10], whose study had a mean follow-up period of 37 months. Short-term and medium-term cure rates for anterior vaginal wall repair with a Gynemesh TM PS range from 90% to 100% [10][11][12][13].…”
Section: Discussionsupporting
confidence: 91%
“…The excellent anatomical results of our study correspond with the 89% objective cure rate reported by de Tayrac et al [10], whose study had a mean follow-up period of 37 months. Short-term and medium-term cure rates for anterior vaginal wall repair with a Gynemesh TM PS range from 90% to 100% [10][11][12][13]. Although there are a variety of forms and sizes, reinforcement of anterior wall defects with a polypropylene mesh provides a superior anatomical result compared with a traditional anterior colporrhaphy or a repair with absorbable mesh [4][5][6].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In studies with apical fixation or concomitant apical surgery [71][72][73][74][75][76][77][78][79], anterior repair using a synthetic mesh (excluding Prolift ® and Perigee ® ) had a cumulative success rate of 93 %; the cumulative success rate of studies without apical fixation or without standard apical surgery [80][81][82][83][84][85][86][87][88][89] was 83 %. The cumulative rate of mesh erosion was 8 % (137/1740); the cumulative rate for chronic pain and de novo dyspareunia was 7% (59/846).…”
Section: Level Of Evidence 3 Grade Of Recommendation Bmentioning
confidence: 99%